EFL LEARNERS’ PERCEPTION TOWARDS THE ONLINE LEARNING - Didi Hermawan (Educational Tracker, 2022)
The purpose of the study is to describe perception of students on online learning. The research is a qualitative that employs a case study as the method of the research. It focuses on how they face online learning. The researcher took the data from the students in the first semester. The first semester students are regular students and workers (have part-time job while studying). To collect the data, each student was interviewed. The interview applied was semi-structured; a type of interview in the category of in-depth interviews, for instance, interviews that are more freely conducted when compared to structured interviews. The analyses from the students’ perception show that online learning is ineffective and most of students feel uninterested. They like teaching and learning in the classroom. Furthermore, some troubles in online learning emerged such as losing connection and adjusting with the online class (zoom / google meeting). The unclear and less interaction also become the problem of online learning. It needs of course several meetings offline at least in one semester. However, online learning should be applied for the students who cannot attend to classroom. Based on the interview, tools for online learning to use are WhatsApp, google classroom, google meeting, and Zoom meeting. In addition, the result of the research shows that the most interesting tool that the student use is zoom meeting since the students are able to experience face to face interaction either to the lecturers or the other students. Although there is sometimes a problem from the signal, they can communicate and ask directly to the lecturer at least. For the future, Hybrid learning can be employed as the technology grows.